Batas Deteksi dan Sensitivitas Metode Deteksi Staphylococcus aureus dalam Sediaan Obat - Nur Aini; Sitoresmi Triwibowo (Fakultas Farmasi Universitas Pancasila, 2023)
Stapylococcus aureus is a pathogen that should be absent in pharmaceutical products. Contamination of certain microorganisms can potentially reduce or inactivate therapeutic activity, affect the stability, efficacy and cause infection of the patient. Microbial detection methods must be valid and sensitive to detect the contamination of microorganisms at low concentrations. The standard method of S. aureus refers to the Indonesian Pharmacopoeia (FI). LOD and sensitivity of the method in general is not stated in FI. This study aims to determine LOD and sensitivity of S. aureus method on pharmaceutical products with route of administration in cutan, oromucosal, gingival, auricular, vaginal and oral based on Indonesian Pharmacopoeia. Experiments used nine pharmaceutical products representing six dosage forms contaminated with S. aureus ATCC 6538 with three level concentrations of ±1, ±3, and ±5 CFU per g atau mL sample. LOD and sensitivity were determined and analyzed descriptively. This study shows that the detection limit is 1-3 colonies per g or mL sample and a sensitivity of 100%. Results of this study can be used as reference for LOD value in the validation or verification process of the S. aureus detection method in the laboratory to ensure validity of the methods used.